2018
DOI: 10.1111/dom.13318
|View full text |Cite
|
Sign up to set email alerts
|

Switching from sitagliptin to liraglutide to manage patients with type 2 diabetes in the UK: A long‐term cost‐effectiveness analysis

Abstract: Switching from sitagliptin 100 mg to liraglutide 1.8 mg in patients with poor glycaemic control was projected to improve clinical outcomes and is likely to be considered cost-effective in the UK setting and, therefore, a good use of limited NHS resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Empagliflozin and canagliflozin have both demonstrated cost-effectiveness vs. comparators in the UK [62][63][64]. Several studies of liraglutide in the UK have also concluded costeffectiveness, despite increased acquisition cost, due to reduction in diabetes-related complications [65][66][67]. However, cost-effectiveness analyses evaluate drugs as glucoselowering entities, and modelling is therefore based on traditional risk equations [68][69][70][71], which do not capture potential cardiovascular benefits [72].…”
Section: Therapy Choices Based On Cost-effectiveness Analysesmentioning
confidence: 99%
“…Empagliflozin and canagliflozin have both demonstrated cost-effectiveness vs. comparators in the UK [62][63][64]. Several studies of liraglutide in the UK have also concluded costeffectiveness, despite increased acquisition cost, due to reduction in diabetes-related complications [65][66][67]. However, cost-effectiveness analyses evaluate drugs as glucoselowering entities, and modelling is therefore based on traditional risk equations [68][69][70][71], which do not capture potential cardiovascular benefits [72].…”
Section: Therapy Choices Based On Cost-effectiveness Analysesmentioning
confidence: 99%
“…Of the 864 identified studies, 56 studies were eligible for the meta-analysis (see figure 1). From the 56 studies, 82 comparisons were assessed, including GLP1 versus DPP4i (n=10) [18][19][20][21][22][23][24][25][26][27] ; GLP1 versus sulfonylureas (n=7) 20 25-30 ; GLP1 versus thiazolidines (n=3) 21 30 31 ; GLP1 versus insulins (n=27, 23 HICs 19 30-52 and 3 UMICs [53][54][55] ); GLP1 versus insulin plus DPP4i (n=2), 45 56 or insulin plus sulfonylureas (n=2), 52 57 GLP1 versus insulin plus GLP1 (n=5) 36 42 46 55 58 and insulin degludec/liraglutide (IDeg-Lira) versus insulin (n=7). 34-36 42 46 48 59 Among GLP1s, treatment comparisons included liraglutide versus exenatide (n=7) 43 56 60-64 and liraglutide versus lixisenatide (n=5).…”
Section: Resultsmentioning
confidence: 99%
“…INBs of GLP1 versus DPP4i were estimated (n=10 [18][19][20][21][22][23][24][25][26][27] ), and all were from HICs with no heterogeneity (I 2 =0, figure 2A). The INB p was US$4012.21 (95% CI US$−571.43 to US$8595.84), which favours GLP1 compared with DPP4i, but does not reach statistical significance.…”
Section: Glp1 Versus Dpp4imentioning
confidence: 99%
“…Overall, 38 studies reporting health economic analysis of antidiabetic medications were included, with one study reporting evaluations for three countries of interest [ 30 , 51 , 70 105 ]. Of the 40 evaluations, most were for the UK ( n = 23), followed by Spain ( n = 9) and Italy ( n = 4), with two each from France and Germany.…”
Section: Resultsmentioning
confidence: 99%